Prevalence of microorganisms resistant to ciprofloxacin isolated in urinary tract infections at University Hospital of Recife/PE (Research, Society and Development, 2022)
Urinary tract infection (UTI) is one of the main causes of medical consultation, second only to respiratory infections. The main etiologic agent is the bacterium Escherichia coli, but other bacteria, such as Klebsiella pneumoniae, Proteus spp., Enterobacter spp., may also be involved. Ciprofloxacin, from the quinolone class, is the drug of choice to treat UTI. It has high absorption capacity, good coverage by gram-negative bacteria and is available both orally and intravenously. However, microbial resistance to this class of drugs has been increasing. The present study aimed to identify, through the CCIH database of the HC-UFPE, the prevalence of ciprofloxacin-resistant microorganisms in patients with UTI. The research was a cross-sectional study on data from patients with UTI from January to December 2019, with CEP approval under CAAE number 20644719.3.3001.8807. The results showed that, of the 301 positive urine cultures, 82 showed resistance to ciprofloxacin. The most prevalent bacterium was E. coli. Most cases of infection affected women, with 193 female patients, 104 men and 4 newborns. Regarding the clinic, nephrology patients were the ones with the most UTIs. Growing resistance to ciprofloxacin may limit effective therapeutic options for treating UTI, and one of the causes is the indiscriminate and abusive use of antimicrobials. To minimize this situation, it is necessary to alert and make the population aware of the dangers and risks of using antimicrobials without a medical prescription and in the wrong way.